DECISION MAKING IN NICHOLAS SPARK'S DEAR JOHN - Tania mandias; Mister Gidion Maru; Merlin Maukar (SoCul: International Journal of Research in Social Cultural Issues, 2021)
The aim of this study is to reveal about the decision making by Savannah and John in their love relationship in Nicholas Sparks’ Dear John. The writers employ qualitative method in conducting this research and in the data collection, the writers use primary source: the work itself Nicholas Sparks’ Dear John and secondary source: another references such as journals, books or internet sources which related and relevant to the research. In term of data analysis, the writers use psychoanalytic approach because decision making is so related with thoughts, emotions and environment. The study shows that when they are in a long distance relationship, they make a wrong decision too soon to end up their relationship just because of time, situation and feeling and they still love each other deeply when they meet again but it is too late to turn around the situation because Savannah has become someone else’s wife and it is impossible to break their mariage. The result of this study shows that when making a decision, John and Savannah prefer in id which means that they make a decision just because of their immediate satisfication that every wishful or pleasure should be satisfied without thinking about the consequences, if it brings a damage or profit in their future.